Chlorine-mediated photocatalytic hydrogen production based on triazine covalent organic framework - Li, Shuang; Wu, Mei-Feng; Guo, Tao; Zheng, Ling-Ling; Wang, Dengke; Mu, Yi; Xing, Qiu-Ju; Zou, Jian-Ping (Applied catalysis. B, Environmental, 2020)
A novel strategy was firstly developed to prepare Cl intercalated CTF-1 photocatalyst (labeled as Cl-ECF) via ball-milled flaking assisted acidification. The Cl-ECF exhibited enhanced photocatalytic activity of H2 production because Cl-C and Cl-N covalent bonds can form covalently interlayer channels in the Cl-ECF that can significantly promote photogenerated charge transfer. [Display omitted] •A new strategy was developed for synthesis of Cl-intercalated CTF-1.•Cl-C and Cl-N bonds can be formed in the Cl-intercalated CTF-1.•Cl-C and Cl-N covalent bonds can form covalently interlayer channels to promote charge transfer.•The Cl-intercalated CTF-1 show superior photocatalytic hydrogen evolution. Covalent triazine-based frameworks (CTFs), as a type of 2D conjugated polymer, have attracted keen attention because of the promising visible-light-driven photocatalytic performance for water splitting. Nonetheless, amelioration on the configuration and electronic microstructure of CTFs for enhanced photocatalytic performance is still challenging and anticipated. Herein, we developed a new strategy to synthesize visible-light-driven Cl-intercalated CTF-1 photocatalysts (labeled as Cl-ECF) via a ball-milling exfoliation-assisted acidification method. Many characterizations confirm the formation of Cl-C and Cl-N bonds in the Cl-ECF. The effects of the Cl-intercalation on the crystal structure, microstructure and charge transfer behaviors of CTF-1 were systematically studied by various characterizations and DFT calculation. The results revealed that Cl-ECF exhibited significantly promoted charge transfer, narrowed bandgap and enhanced photocatalytic activity of H2 production because Cl-C and Cl-N covalent bonds can form covalently interlayer channels in the Cl-ECF. The as-prepared Cl-ECF shows a hydrogen production rate of 1.296 mmol·g–1 h–1 under visible light irradiation, which is 2.2 times higher than that of CTF-1. This work could provide new insights into the new approach of intercalation modification to improve photocatalytic performance of 2D layered photocatalysts.